Efektivitas Insentif Pajak Restoran Selama Masa Pandemi Covid-19 Tahun 2021 Sebagai Pendapatan Asli Daerah Di Badan Pengelola Keuangan Daerah (BPKD) Kota Tangerang - Siti Nur Annisa Rachmat Nur Annisa Rachmat; Erni Prasetiyani (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
This research is carried out to find out how the effectiveness of the Restaurant Tax Incentive Policy provided by the Regional Government and The Original Income of the Tangerang City Region during the Covid-19 Pandemic period in 2021, where in 2020 in January to February the PAD of Tangerang City has experienced an increase in revenue realization by 1.09% exceeding the target of reaching IDR 3.64 billion from originally only IDR 3.6 billion. However, the increase could not last long because in May 2020, PAD of Tangerang City immediately experienced a decrease in revenue to only reach Rp 68 billion, that previously could reach Rp 200 billion. This research uses Qualitative research methods with a descriptive approach. The technique of data collection used in this study is by documentation, interview and observation. The results of this study show that the Tax Incentive policy in 2021 has been running with an effect and the Regional Original Income (PAD) of Tangerang City could also gradually improve and can achieve the target, from the target income of IDR 135 billion, PAD of Tangerang City gets more than IDR 153 billion, although the 2021 revenue target is relatively lowered in the previous year.